2012
DOI: 10.1186/1478-4505-10-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical practice guidelines within the Southern African development community: a descriptive study of the quality of guideline development and concordance with best evidence for five priority diseases

Abstract: BackgroundReducing the burden of disease relies on availability of evidence-based clinical practice guidelines (CPGs). There is limited data on availability, quality and content of guidelines within the Southern African Development Community (SADC). This evaluation aims to address this gap in knowledge and provide recommendations for regional guideline development.MethodsWe prioritised five diseases: HIV in adults, malaria in children and adults, pre-eclampsia, diarrhoea in children and hypertension in primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
75
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(82 citation statements)
references
References 24 publications
6
75
1
Order By: Relevance
“…[1][2][3] With the emergence of international collaborations such as the Guidelines International Network (G-I-N), [4] there have been concerted attempts to standardise CPG writing practices across countries, to increase the credibility of the final products. [5][6][7] Without adherence to rigorous guideline development and reporting standards, the considerable time and effort put into developing guidelines may be wasted, as intended users may not have confidence in the recommendations made.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] With the emergence of international collaborations such as the Guidelines International Network (G-I-N), [4] there have been concerted attempts to standardise CPG writing practices across countries, to increase the credibility of the final products. [5][6][7] Without adherence to rigorous guideline development and reporting standards, the considerable time and effort put into developing guidelines may be wasted, as intended users may not have confidence in the recommendations made.…”
mentioning
confidence: 99%
“…However, there is room for improvement if SA CPG activities are to match global standards. [7] In April 2014, the SAMJ signalled on its website the appointment of an editorial subcommittee whose specific mandate would be to review guidelines submitted for publication. The SAMJ has regularly published guidelines and recommendations for the management of a variety of conditions.…”
mentioning
confidence: 99%
“…In most cases, CHWs in low-income contexts are poor and usually female [57,58]. Expecting economically marginalised women to provide health and welfare services to others, without remuneration, has been argued to amount to labour exploitation [24,59].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that implementation of evidence-based treatment guidelines is effective in reducing antimicrobial resistance and hospital-acquired infections when used appropriately [66]. A survey on use of inpatient treatment guidelines for HIV in adults, malaria in children and adults, pre-eclampsia, diarrhea in children, and hypertension in the Southern Africa Development Community (SADC) identified substantial gaps in quality of evidence in available guidelines and the extent to which they were implemented [67]. These findings are consistent with the reality that most health facilities in Africa have not yet adopted standard treatment guidelines and, even where they exist, adherence may prove to be very low.…”
Section: Back To Realitymentioning
confidence: 99%